Effect of Rivastigmine Augmentation in Treatment of Male Patients With Combat-Related Chronic Posttraumatic Stress Disorder: A Randomized Controlled Trial. Issue 1 (February 2017) - Rezaei Ardani, Amir; Hosseini, Golkoo; Fayyazi Bordbar, Mohammad Reza; Talaei, Ali; Mostafavi Toroghi, Hesam
Abstract: Background: Posttraumatic stress disorder (PTSD) is one of the chronic and disabling psychiatric disorders, particularly in combat veterans. In a case series, rivastigmine was suggested to be an effective augmentation in treatment of PTSD. The aim of the present study was to evaluate this finding in a randomized controlled trial. Method: A 12-week, double-blind, placebo-controlled clinical trial was performed on 36 male patients (aged 42–60 years) diagnosed with chronic, combat-related PTSD. Subjects were screened for apparent cognitive deficits by means of Mini-Mental State Examination. All patients received selective serotonin reuptake inhibitors plus sodium valproate for 4 weeks and then reevaluated. Subjects who did not show adequate response were randomly assigned into 3 groups receiving rivastigmine (up to 6 mg/d), placebo, or the prior treatment regimen. Efficacy of medication was measured by administering PTSD Check List–Military Version at baseline and weeks 2, 4, 8, and 12. Collected data were analyzed by analysis of variance and repeated measurement. Reported differences were considered significant at the level of 0.05 or less. Results: The 3 groups showed statistically significant reductions in the total PTSD Check List–Military Version, avoidance subscale, and the reexperience subscale but not in the hyperarousal subscale. No significant differences were found between the 3 groups. Conclusions: In contrast to the previous case series, findings of the current study did not support the efficacy of adjunctive rivastigmine in treatment of PTSD. This hypothetically could be due to the fact that all the study's subjects scored higher than 25 on Mini-Mental State Examination.